2014
DOI: 10.1055/s-0034-1390419
|View full text |Cite
|
Sign up to set email alerts
|

DPP-4 Inhibitor Teneligliptin Improves Insulin Resistance and Serum Lipid Profile in Japanese Patients with Type 2 Diabetes

Abstract: Dipeptidyl peptidase-4 (DPP-4) inhibitors have been reported to improve the glycemic control and blood hemoglobin A1c (HbA1c) concentrations. However, there are few reports as yet suggesting that DPP-4 inhibitors may also improve insulin resistance and the serum lipid profile in the clinical setting. This study was aimed at investigating the effect of 14-week treatment with teneligliptin (20 mg/day) on the homeostasis model assessment ratio (HOMA-R), an indicator of insulin resistance, and serum lipid profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
5
14
0
Order By: Relevance
“…Importantly, no significant differences were found between teneligliptin and sitagliptin in lipid profiles or glycaemic variability. Both teneligliptin and sitagliptin improved insulin resistance, based on HOMA‐β, which is in line with previous data showing the positive impact of teneligliptin on insulin resistance …”
Section: Discussionsupporting
confidence: 91%
“…Importantly, no significant differences were found between teneligliptin and sitagliptin in lipid profiles or glycaemic variability. Both teneligliptin and sitagliptin improved insulin resistance, based on HOMA‐β, which is in line with previous data showing the positive impact of teneligliptin on insulin resistance …”
Section: Discussionsupporting
confidence: 91%
“…This study is the first to demonstrate this causal relationship using ETIrs2KO mice; we showed that chronic treatment with anagliptin enhanced insulin-induced capillary recruitment and interstitial insulin concentrations, thereby improving the skeletal muscle glucose uptake in vivo, by directly acting on endothelial cells via NO-and GLP-1-dependent mechanisms. The findings of our study may be of clinical relevance, as GLP-1R agonists and DPP4 inhibitors have been reported to attenuate insulin resistance in humans [9][10][11]40]. Taken together, these data suggest that anagliptin might be a promising agent to improve skeletal muscle insulin resistance in obese patients with type 2 diabetes.…”
Section: Discussionsupporting
confidence: 62%
“…Thus, anagliptin treatment may improve insulin resistance in OLETF rats. Indeed, previous studies showed that another DPP-4 inhibitor, teneligliptin, improved insulin resistance in type 2 diabetic patients (26) and that anagliptin ameliorated insulin resistance in the mouse liver (27). The issue of whether treatment with miglitol or anagliptin ameliorates insulin resistance in OLETF rats should be further assessed using insulin tolerance tests.…”
Section: Discussionmentioning
confidence: 99%